PEMENUHAN HAK ANAK ATAS PENDIDIKAN KESEHATAN REPRODUKSI DI KOTA BATAM - Idilianti, Idilianti (Universitas Internasional Batam, 2020)
Sexual growth on teenagers should be followed by sexual education. However, sexual education is still a polemic and a most debated topic among people. This research is a socio-legal research, thus it uses primary data supporte by secondary data. It was found that the implemention of children?s rights of sexual education based on the Government Decree Number 61 of 2014 on Reproduction Health at Batam City, particulaly in Public Health Center (PUSKESMAS) has not been effectively conducted. The obstacles faced by Public Health Center are limited resources, time, and budget. To overcome these obstacles, the research suggests that all relevant parties to get involved in implementing a comprehensive reproductive health education in accordance with the mandate of the Law and improving the skills of personnel resources, facilities and infrastructure relating to reproductive health education. In addition, an establishment of Regional Regulations and / or the decision of the Regional Head which requires a cross-agency coordination at the government so that the fulfillment of children's right to reproductive health education can be carried out in a comprehensive manner.